Knowledge Level of Mothers Who Have Toddlers About Fever Seizures in Toddlers in Huta Koje Village, Southeast Padangsidimpuan District, Padangsidimpuan City in 2020 - Desi Meliana Gultom (LLDIKTI Wilayah 1, 2021)
Febrile seizures are seizures that occur when an increase in body temperature is caused by a step process, usually occurs in children aged 3 months to 5 years and can be repeated when a child has a febrile seizure for the first time at an early age. This study aims to determine the level of knowledge of mothers with toddlers about febrile seizures in toddlers in Huta Koje Village, Southeast Padangsidimpuan District, Padangsidimpuan City. Can be measured by 3 categories, namely good knowledge, sufficient, and less. the method used is a descriptive method using a questionnaire about the characteristics based on age, education, occupation and sources of information. This research was conducted on 73 mothers as samples taken from the door to door technique. The results of the study are presented in the distribution of frequencies and percentages. From the results of the study found that the knowledge of respondents with good knowledge is 7 people (9.6%), knowledgeable enough is 36 people (49.4%), and less knowledgeable is 30 people (41%). It was concluded that the level of knowledge of mothers with toddlers about febrile seizures in toddlers in Huta Koje Village, Southeast Padangsidimpuan District, Padangsidimpuan City in 2020, the majority of their knowledge was sufficient knowledge.